2014
DOI: 10.1016/j.ejca.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor regarding the paper by Aurilio et al., A meta-analysis of oestrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 discordance between primary breast cancer and metastases

Abstract: Sir,We have read with great interest the article in press of Aurilio et al., A meta-analysis of oestrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 discordance between primary breast cancer and metastases (http://dx.doi.org/10.1016/j.ejca.2003. 10.004), which will appear in Eur J Cancer. In the paper, the Authors have performed a meta-analysis of the studies published in the literature concerning the discordance rate in oestrogen receptor (ER), progesterone receptor (PgR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Indeed HER2 status has been identified as a significant additional prognostic parameter in advanced GC [ 28 ]. Interestingly, the possible discordance in HER2 status between primary tumour and matched metastases has been shown in both breast and stomach cancers [ 7 , 9 , 10 , 11 , 15 , 19 , 24 , 25 , 29 , 30 ]. As a consequence, the need to assess HER2 status not only in the primary tumour, but also in its metastases, was recently emphasized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed HER2 status has been identified as a significant additional prognostic parameter in advanced GC [ 28 ]. Interestingly, the possible discordance in HER2 status between primary tumour and matched metastases has been shown in both breast and stomach cancers [ 7 , 9 , 10 , 11 , 15 , 19 , 24 , 25 , 29 , 30 ]. As a consequence, the need to assess HER2 status not only in the primary tumour, but also in its metastases, was recently emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the need to assess HER2 status not only in the primary tumour, but also in its metastases, was recently emphasized. However, studies investigating the changes in HER2 status mainly considered recurrent, loco-regional or metachronous lesions, while modification in HER2 status between paired primary neoplasm and synchronous nodal metastases was explored in only a few analyses [ 15 , 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression or amplifi cation of human epidermal growth-factor receptor 2 (HER2) frequently occur in primitive neoplastic tissues from patients with breast carcinoma (BC). [1][2][3][4] However, in recent years, several studies have demonstrated that HER2 status may vary in the metastatic lesions compared to the primary tumor, [5][6][7][8] and this discrepancy is more frequently found in distant metastases than in loco-regional ones. [9][10][11][12][13] Discordance in HER2 status was not only found between primary BC and its metastases, but also among the consecutive relapses of the same tumor, with similar proportions of cases turning from negative to positive or vice versa and the changes mainly appeared in the second or following progressions.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] For this reason, some investigators proposed that detection of HER2 status should be re-assessed in the neoplastic tissues from metastatic BC to establish whether the therapy is actually appropriate. [1,2,16,17] Thus, in this study, we evaluated HER2 status in paired samples of BC/GC and synchronous metastatic lymph nodes that were collected during the same surgical and tissue processing procedures, thus limiting and avoiding any potential technical bias due to external factors. Our aim was to explore the eventual HER2 discordance rate between primary BC and GC samples and corresponding lymph node metastases.…”
Section: Introductionmentioning
confidence: 99%